A study of Benguela Niños and Niñas from 1958 to 2015 - Imbol, Koungue Rodrigue Anicet (Department of Oceanography, 2019)
Prediction and Research Moored Array in the Tropical Atlantic (PIRATA) records in combination with outputs from an Ocean Linear Model (OLM) and altimetric data are used to investigate the link between the equatorial Atlantic Ocean dynamics and the variability in the coastal region of Angola-Namibia at interannual timescales over 1998 to 2012. The PIRATA records help to define an index of equatorial Kelvin wave activities in the Equatorial Atlantic. There is a good agreement between PIRATA monthly dynamic height anomalies, altimetric monthly sea surface height anomalies (SSHA), and sea level anomalies calculated with an OLM at interannual time scales. This allows the interpretation of PIRATA records in terms of equatorial Kelvin wave propagations. Extreme warm or cold events in the Angola – Namibia area lag strong anomalous eastward equatorial propagations by 1–2 months. Remote equatorial forcing via equatorial Kelvin waves which propagate poleward along the west African coast as coastal trapped waves is at the origin of their developments. Results show a seasonal phasing, with significantly higher correlations between the equatorial index and coastal sea surface temperature anomalies (SSTA) off Angola-Namibia in October - April season. Then, a systematic study of all the Benguela Niño and Benguela Niña events before 1982 is done using an Ocean general circulation model in combination with the OLM outputs from 1958 to 2015. 26 anomalous strong coastal events (16 warm and 10 cold) are identified. The analysis of their evolution confirms the remote equatorial origin of most of these coastal anomalous strong events. Modelled meridional transport anomalies across the Angola Benguela Front (ABF) contribute to the development of these anomalous coastal warm events. Across the ABF, the results obtain with the net temperature transport are similar to the ones with net mass transport. Most anomalous events peak in October - April season. Lagged composites of surface temperature and wind stress anomalies in the equatorial and southeastern Atlantic reveal that both local and remote forcings develop simultaneously 1-2 months before the peak of Benguela Niño or Niña. At the monthly scale, local atmospheric forcing is more correlated with anomalous coastal events occurring in Southern Angola which is a non-wind-upwelling driven region. The results from this thesis open the possibility to predict Benguela Niño and Benguela Niña events using an index depicting the equatorial interannual variability associated with Interannual Equatorial Kelvin Wave propagation, especially from October to April when the coastal stratification is favourable to the imprint of coastal trapped waves in the surface layer.